(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This study examines the Safe School Initiative programme and human security in Nigeria. Safe School Initiative was introduced in Nigeria in 2014 to protect students in schools and provide a safe school environment that supports the smooth implementation of teaching and learning in schools. The implementation of the school initiative programme has since commenced in the North-East region of Nigeria. This paper discussed the implementation challenges of the Safe School Initiative programme in Nigeria. The paper employed the documentary research method, while content analysis was the method of data analysis. Therefore, secondary data were collected from both print and online publications. Content analysis was used to analyze the selection of literature for the study. The study revealed that the challenges such as funding shortage, corruption, weak monitoring and evaluation, poor involvement of stakeholders, insecurity problems and lack of political will that affected the implementation of the Safe School Initiative Programme hindered the achievement of human security. Based on the findings of this study, the paper recommends that both federal and state governments should work cooperatively to ensure adequate funding, enhance effective monitoring and evaluation systems, involvement of critical stakeholders and the establishment of community and city policing for the Safe School Initiative. The suggested solution will address security challenges, create a conducive learning environment for students and enhance their human security.